COMMON RISK FACTORS FOR THE DEVELOPMENT OF ANTI TUBERCULOSIS TREATMENT INDUCED HEPATOTOXICITY - Abbasi, Munir Ahmad; Ahmed, Naseer; Suleman, Amir; Zaman, Haidar; Tariq, Sumbal; Anwar, Syed Abbas; Khan, Nisar (Journal of Ayub Medical College Abbottabad, 2014)
Background: Tuberculosis is a global pandemic which affects millions of people every year. The treatment of tuberculosis consists of simultaneous use of a number of drugs for a prolonged period of time, therefore anti-tuberculosis treatment induced toxicity is a real problem. Many risk factors which make a tuberculosis patient prone to the development of hepatotoxicity associated with the anti-tuberculosis treatment have been identified. The aim of this study was to determine common risk factors responsible for precipitation of hepatotoxicity following treatment with anti-tuberculosis drugs. Methods: This cross-sectional study was conducted in the Department of Pulmonary Medicine, Ayub Teaching Hospital, Abbottabad from20th April 2013to19th March 2014. Patients who were newly diagnosed cases of tuberculosis in whom treatment of tuberculosis with first line anti-tuberculosis drugs was initiated and were 20 years or older, were included. The precipitation of drug induced hepatotoxicity was diagnosed with detailed history taking and physical examination followed by laboratory investigations, i.e., Liver Function tests (LFT). Results: Of the total 179 patients included in this study, 100 (55.8 %) were males and 79 (44.2 %) were females. Out of them 23 (12.85%) developed hepatotoxicity. Drug induced hepatotoxicity was observed in the older patients. No relationship was found with the sex, body mass index (BMI), and pre-existing liver disease. Conclusion: The study showed that the risk of development of drug-induced hepatotoxicity following treatment with first line anti-tuberculosis treatment increased with the age of the patient. Keywords: Tuberculosis, Anti-Tuberculous Therapy, Liver disease, Body Mass Index, Hepatotoxicity